The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/chem.202001990
|View full text |Cite
|
Sign up to set email alerts
|

Permethylated NHC‐Capped α‐ and β‐Cyclodextrins (ICyDMe) Regioselective and Enantioselective Gold‐Catalysis in Pure Water

Abstract: As eries of water-soluble encapsulatedc opper(I), silver(I) or gold(I)c omplexes based on NHC-capped permethylatedc yclodextrins (ICyD Me)w ere developed andu sed as catalysts in pure water for hydration, lactonization, hydroarylation and cycloisomerization reactions. ICyD Me li-gands gave cavity-based high regioselectivity in hydroarylations, and high enantioselectivities in gold-catalyzed cycloisomerizations reactions giving up to 98 % ee in water.T hese ICyD Me are therefore useful ligandsf or selectivec at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 111 publications
(142 reference statements)
0
19
0
Order By: Relevance
“…A prerequisite for a detailed study of the electronic effects involving the coinage metal encapsulated in the cyclodextrin cavity of an ICyD ligand is to get a crystal structure. We have shown that the replacement of benzyl groups with methyls on ICyD ligands could lead to the crystallization of (α‐ICyD Me )AgCl [39] . We also previously synthesized (α‐ICyD Me )CuCl, (α‐ICyD Me )AgCl, and (α‐ICyD Me )AuCl and characterized them by NMR.…”
Section: Resultsmentioning
confidence: 99%
“…A prerequisite for a detailed study of the electronic effects involving the coinage metal encapsulated in the cyclodextrin cavity of an ICyD ligand is to get a crystal structure. We have shown that the replacement of benzyl groups with methyls on ICyD ligands could lead to the crystallization of (α‐ICyD Me )AgCl [39] . We also previously synthesized (α‐ICyD Me )CuCl, (α‐ICyD Me )AgCl, and (α‐ICyD Me )AuCl and characterized them by NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, using [Tol‐BINAP(AuCl) 2 ] as precatalyst we only achived good results with one substrate with a phenyl‐substituted alkyne [17] . Since then, other groups achieved moderate enantioselectivities with chiral gold(I) catalysts, [18, 19] the exception being the recent elegant work of Sollogoub, Fensterbank, and Mouriès‐Mansuy using NHC‐capped β‐cyclodextrin gold(I) catalysts, which led to up to 94–98 % ee in the hydroxy‐ and methoxycyclization of 1,6‐enynes [14d,e] . However, being based on cyclodextrins, these catalysts only provide one of the two possible enantiomeric forms of the final cyclized products.…”
Section: Methodsmentioning
confidence: 99%
“…[ 37 , 38 ] Thus, using NHC‐capped β‐cyclodextrin gold(I) catalyst 31 , the Sollogoub group achieved excellent enantioselectivities (up to 94–98 % ee ) in the hydroxy‐ and methoxycyclization of 1,6‐enynes 14 (Scheme 8 ). [ 37c , 37d ]…”
Section: Intramolecular Gold(i)‐catalyzed Transformationsmentioning
confidence: 99%